Modelling of Functional Interaction of Hybrid Energy Storage System Battery Units - K. V. Dobrego; I. A. Koznacheev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Optimization of technical and economic parameters of electric power storage devices is a necessary condition for their widespread use. The article develops a general approach and proposes a methodology for assessing the economic efficiency of hybridization of electrochemical energy storage systems (ESSs). From the point of view of evaluating the effectiveness of storage hybridization, a number of model systems operating under different load conditions using different block functional interaction schemes are being investigated. Lead-acid batteries supplemented with lithium-ion batteries; lead-acid batteries supplemented with supercapacitors and lithium-ion batteries supplemented with supercapacitors are considered as the basic types of hybrid storage devices. An electric forklift, a 30-apartment residential building, as well as a 300-apartment residential complex are considered as the load of the ESS. A quantitative and qualitative model for evaluating the effectiveness of hybridization is used, based on comparing the cost of buffering electricity by each type of battery and the hybrid drive as a whole. For all cases, economic indicators characterizing the cost of buffering electricity by hybrid ESSs are calculated and the advantages of a particular scheme of interaction of hybrid ESS blocks are analyzed. It is shown that the hybridization efficiency demonstrates a complex nonlinear dependence on the degree of hybridization, the type of which depends both on the type of batteries used and on the nature of the load schedule, as well as on the type of functional interaction of the blocks. A specific feature of this dependence is a sharp increase in economic efficiency at small values of a £ 0.01 and a further slowdown in the growth or fall of the graph. The obtained results make it possible to quantitatively compare the efficiency of the hybridization of the ESS for specific conditions of its operation. The considered models and methods can be used in the design of ESSs and “generator – storage – consumer” systems, assessment of the economic feasibility of hybridization of ESSs.